PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KONTRAK ROCKY HOTEL PADANG DENGAN MOTIVASI KARYAWAN SEBAGAI MEDIASI - Nora Damayanti; Yulihasri Yulihasri (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This study aims to analyze the effect of compensation, organizational culture on employee performance and work motivation as mediation for Rocky Hotel Padang contract employees. This study uses primary data obtained by distributing questionnaires to Rocky Hotel Padang contract employees. Sampling was carried out using the census method. The sample in this study amounted to 100 questionnaires. In this study the authors used the PLS - SEM analysis technique.The results showed that compensation, organizational culture had a positive effect on the performance of Rocky Hotel Padang contract employees, both directly and indirectly. The performance of Rocky Hotel Padang contract employees was 88.6% influenced by compensation, organizational culture, and motivation of contract employees of Rocky Hotel Padang 64.8% were affected by compensation, organizational culture, and the rest were influenced by other variables not examined in the study this. Keywords: Compesation, Organization Culture, Motivation, Employee Performance